Pengaruh Desain Produk dan Harga Terhadap Keputusan Pembelian Gitar Pada Toko JS Music Di Sukoharjo - Nurul Azizah Nur Fatimah; Muhammad Syihabuddin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of product design and price on guitar purchasing decisions at the JS Music Store in Sukoharjo. The population of this study was the Sukoharjo community totaling 916,472 people as potential consumers, with a sample of 100 respondents obtained through the distribution of Likert scale questionnaires. The analysis method used was multiple linear regression with validity and reliability tests, classical assumption tests, as well as t-tests and coefficients of determination. The results showed that product design had no significant effect on purchasing decisions, while price had a significant effect on guitar purchasing decisions at the JS Music Store. The customized R-square value of 0.338 indicates that product design and price contributed 33.8% to purchasing decisions, while 66.2% was influenced by other factors outside this study. This finding confirms that price is the dominant factor in influencing consumer purchasing decisions, while design only plays a role as added value and not as the main factor.